PERAN KEPALA SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH DASAR NEGERI - Nafazri Eprilia; Deviyanti Pangestu; Yulita Dwi Lestari (STKIP Subang, 2024)
This study aims to 1) identify and describe the role of the principal in managing elementary school education. 2) knowing the factors that support and inhibit the improvement of the quality of elementary school education at SD N in Way Lima, Pesawaran Regency. Draft research used is descriptive qualitative. Using sheets interviews with 3 informants, namely the principal, deputy principal and teacher, as well as observation sheets were used to determine school facilities and infrastructure. From the results of the study it can be concluded that in improving the quality of education the principal performs his role as 1) educator. 2) managers. 3) administrators. 4) supervisors. 5) leader. 6) an innovator and 7) a good motivator, the school principal provides sanctions according to existing regulations, and regulates the implementation of an adequate work atmosphere. Based on the results of interviews, observations and documentation obtained, the school principal can be said to have carried out his role properly good.